A subset of liver resident natural killer cells is expanded in hepatitis C-infected patients with better liver function - Erin H. Doyle (Nature Portfolio, 2021)
Abstract Viral hepatitis leads to immune-mediated liver injury. The rate of disease progression varies between individuals. We aimed to phenotype immune cells associated with preservation of normal liver function during hepatitis C virus (HCV) infection. Clinical data and specimens were obtained from 19 HCV-infected patients undergoing liver transplantation. Liver and peripheral blood mononuclear cells were isolated and eight subsets of innate immune cells were delineated by multiparameter flow cytometry. Cytokine assays and microarrays were performed. Intrahepatic CD56Bright/CD16- natural killer (NK) cells comprised the only subset correlating with better liver function, i.e., lower bilirubin (p = 0.0002) and lower model for end stage of liver disease scores (p = 0.03). The signature of liver NK cells from HCV-infected patients included genes expressed by NK cells in normal liver and by decidual NK cells. Portal vein blood had a higher concentration of interleukin (IL)-10 than peripheral blood (p = 0.03). LMCs were less responsive to toll-like receptor (TLR) stimulation than PBMCs, with fewer pro-inflammatory gene-expression pathways up-regulated after in vitro exposure to lipopolysaccharide and a TLR-7/8 agonist. Hepatic CD56Bright/CD16- NK cells may be critical for maintaining liver homeostasis. Portal vein IL-10 may prime inhibitory pathways, attenuating TLR signaling and reducing responsiveness to pro-inflammatory stimuli.